Anodizable Al-Zn-Mn-Mg series die-cast aluminum alloy and preparation method thereof, and aluminum alloy structural member

CN122979718APending Publication Date: 2026-10-27SIHUI HUIHUANG METAL PROD CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611160203.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-09-29
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

在阳极氧化处理的过程中,Mg5Al8相易溶解,会降低成膜效率而无法形成厚度较大的阳极氧化膜,而且得到的阳极氧化膜的均匀度和光泽度也较差

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The application provides an anodizable Al-Zn-Mn-Mg series die-casting aluminum alloy, which contains Zn with a mass percentage of 2-4.5%, Si with a mass percentage of 0.01-0.8%, Fe with a mass percentage of 0.001-0.5%, Cu with a mass percentage of 0.001-0.3%, Mn with a mass percentage of 1-3%, Mg with a mass percentage of 0.8-4%, B with a mass percentage of 0-0.05%, Sn with a mass percentage of 0-0.05%, Sb with a mass percentage of 0-0.2%, In with a mass percentage of 0-0.1% and Bi with a mass percentage of 0-0.5%. The application further provides a preparation method of the anodizable Al-Zn-Mn-Mg series die-casting aluminum alloy and an aluminum alloy structural member.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] This invention is a divisional application. The original application number is 2025114161685, the application date is September 29, 2025, and the title is "Anodizable Al-Zn-Mn-Mg series die-cast aluminum alloy and its preparation method, aluminum alloy structural parts". Technical Field

[0002] This invention relates to the field of aluminum alloy technology, and more particularly to an anodizable Al-Zn-Mn-Mg die-cast aluminum alloy, a method for preparing the anodizable Al-Zn-Mn-Mg die-cast aluminum alloy, and aluminum alloy structural parts. Background Technology

[0003] Aluminum alloys are widely used in structural components of electronic products due to their lightweight, good machinability, excellent mechanical properties, and ease of coloring. To achieve a better appearance, aluminum alloy structural components typically undergo anodizing.

[0004] For Al-Zn based aluminum alloy structural parts, Zn is the main alloying element. When the mass percentage content of Zn is greater than 3%, the presence of Zn will result in a lower applied voltage for the anodizing of aluminum alloy (about 3V lower than that of pure aluminum), making it impossible to form a thick anodic oxide film, and the uniformity and gloss of the obtained anodic oxide film are also poor.

[0005] For Al-Mg aluminum alloy structural parts, Mg is the main alloying element. When the mass percentage of Mg exceeds 3%, the Al-Mg aluminum alloy becomes a heterogeneous alloy, and the Mg5Al8 phase will precipitate. During the anodizing process, the Mg5Al8 phase is easily dissolved, which reduces the film formation efficiency and makes it impossible to form a thick anodic oxide film. Moreover, the uniformity and gloss of the obtained anodic oxide film are also poor.

[0006] Therefore, there is an urgent need for an anodizable die-cast aluminum alloy that not only has better mechanical properties, but also has an anodized film with a certain thickness and a better appearance. Summary of the Invention

[0007] In view of the above-mentioned defects in the prior art, the present invention provides an anodizable Al-Zn-Mn-Mg die-cast aluminum alloy, which aims to make the anodizable die-cast aluminum alloy not only have better mechanical properties, but also have a certain thickness and better appearance of the anodized film on it.

[0008] This invention provides an anodizable Al-Zn-Mn-Mg die-cast aluminum alloy, containing Al, and further containing 2-4.5% Zn, 0.01-0.8% Si, 0.001-0.5% Fe, 0.001-0.3% Cu, 1-3% Mn, 0.8-4% Mg, 0-0.05% B, 0-0.05% Sn, 0-0.2% Sb, 0-0.1% In, and 0-0.5% Bi.

[0009] This invention also provides a method for preparing anodizable Al-Zn-Mn-Mg die-cast aluminum alloys, comprising the following steps: It provides Zn source, Si source, Fe source, Cu source, Mn source, Mg source, B source, Sn source, Sb source, In source, Bi source, and Al source; The Al source is heated to obtain Al liquid; Adding Zn, Si, Fe, Cu, Mn, Mg, B, Sn, Sb, In, and Bi sources to the Al liquid yields an alloy liquid; and The alloy liquid is subjected to forming treatment to obtain an anodizable Al-Zn-Mn-Mg die-cast aluminum alloy, wherein the anodizable Al-Zn-Mn-Mg die-cast aluminum alloy contains 2-4.5% Zn, 0.01-0.8% Si, 0.001-0.5% Fe, 0.001-0.3% Cu, 1-3% Mn, 0.8-4% Mg, 0-0.05% B, 0-0.05% Sn, 0-0.2% Sb, 0-0.1% In, and 0-0.5% Bi.

[0010] The present invention also provides an aluminum alloy structural component, the material of which is the anodizable Al-Zn-Mn-Mg series die-cast aluminum alloy.

[0011] In the technical solution of this invention, the anodizable Al-Zn-Mn-Mg die-cast aluminum alloy contains 2-4.5% Zn, 0.01-0.8% Si, 0.001-0.5% Fe, 0.001-0.3% Cu, 1-3% Mn, 0.8-4% Mg, 0-0.05% B, 0-0.05% Sn, 0-0.2% Sb, 0-0.1% In, and 0-0.5% Bi. The addition of Si, Fe, Cu, Mn, Mg, B, Sn, Sb, In, and Bi within the aforementioned content range, through mutual influence and interaction, can enhance the tensile strength, yield strength, and elongation (over 12%) of the anodizable Al-Zn-Mn-Mg die-cast aluminum alloy to be greater than 310 MPa. This anodizable Al-Zn-Mn-Mg die-cast aluminum alloy is also suitable for anodizing, resulting in an anodized film with not only significant thickness but also excellent transparency, gloss, and color uniformity, making it suitable for manufacturing products with high aesthetic requirements, such as the mid-plate and mid-frame of mobile devices like smartphones. Specifically: Detailed Implementation The technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only a part of the embodiments of the present invention, and not all of them. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0012] An embodiment of the present invention provides an anodizable Al-Zn-Mn-Mg die-cast aluminum alloy, which contains 2-4.5% Zn, 0.01-0.8% Si, 0.001-0.5% Fe, 0.001-0.3% Cu, 1-3% Mn, 0.8-4% Mg, 0-0.05% B, 0-0.05% Sn, 0-0.2% Sb, 0-0.1% In, 0-0.5% Bi, and Al, as well as unavoidable impurities. In the anodizable Al-Zn-Mn-Mg die-cast aluminum alloy, the content of a single impurity does not exceed 0.05%, and the total impurity content does not exceed 0.15%.

[0013] In one embodiment, the anodizable Al-Zn-Mn-Mg die-cast aluminum alloy contains 2-4% Zn, 0.1-0.8% Si, 0.01-0.5% Fe, 0.01-0.3% Cu, 1-2.5% Mn, 1-4% Mg, 0.001-0.05% B, 0.001-0.05% Sn, 0.001-0.2% Sb, 0.001-0.1% In, and 0.001-0.5% Bi.

[0014] The specific mass percentage content of Zn can be 2%, 2.1%, 2.2%, 2.3%, 2.4%, 2.5%, 2.6%, 2.7%, 2.8%, 2.9%, 3%, 3.1%, 3.2%, 3.3%, 3.4%, 3.5%, 3.6%, 3.7%, 3.8%, 3.9%, 4%, 4.1%, 4.2%, 4.3%, 4.4%, or 4.5%. The specific mass percentage content of Si can be 0.01%, 0.02%, 0.04%, 0.06%, 0.08%, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, or 0.8%. The specific mass percentage contents of Fe and Bi can be 0.001%, 0.005%, 0.01%, 0.02%, 0.04%, 0.06%, 0.08%, 0.1%, 0.15%, 0.2%, 0.25%, 0.3%, 0.35%, 0.4%, 0.45%, or 0.5%. The specific mass percentage contents of Cu can be 0.001%, 0.005%, 0.01%, 0.02%, 0.04%, 0.06%, 0.08%, 0.1%, 0.15%, 0.2%, 0.25%, or 0.3%. The specific mass percentage contents of Mn can be 1%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2%, 2.1%, 2.2%, 2.3%, 2.4%, 2.5%, 2.6%, 2.7%, 2.8%, 2.9%, or 3%. The specific mass percentage content of Mg can be 0.8%, 0.9%, 1%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2%, 2.1%, 2.2%, 2.3%, 2.4%, 2.5%, 2.6%, 2.7%, 2.8%, 2.9%, 3%, 3.1%, 3.2%, 3.3%, 3.4%, 3.5%, 3.6%, 3.7%, 3.8%, 3.9%, or 4%. The specific mass percentage content of B and Sn can be 0.001%, 0.002%, 0.003%, 0.004%, 0.005%, 0.006%, 0.007%, 0.008%, 0.009%, 0.01%, 0.02%, 0.03%, 0.04%, or 0.05%. The specific percentage content of Sb by mass can be 0.001%, 0.002%, 0.003%, 0.004%, 0.005%, 0.006%, 0.007%, 0.008%, 0.009%, 0.01%, 0.02%, 0.04%, 0.06%, 0.08%, 0.1%, 0.11%, 0.12%, 0.13%, 0.14%, 0.15%, 0.16%, 0.17%, 0.18%, 0.19%, or 0.2%.The specific percentage content of In by mass can be 0.001%, 0.002%, 0.003%, 0.004%, 0.005%, 0.006%, 0.007%, 0.008%, 0.009%, 0.01%, 0.02%, 0.03%, 0.04%, 0.05%, 0.06%, 0.07%, 0.08%, 0.09%, or 0.1%.

[0015] In one specific embodiment, the mass ratio of Mg to Mn is 0.1-10:1, specifically 0.1:1, 0.2:1, 0.3:1, 0.4:1, 0.5:1, 0.6:1, 0.7:1, 0.8:1, 0.9:1, 1:1, 2:1, 3:1, 4:1, 5:1, 6:1, 7:1, 8:1, 9:1, or 10:1. As the mass ratio of Mg to Mn gradually increases, the yield strength and tensile strength of the aluminum alloy gradually increase; conversely, the elongation of the aluminum alloy gradually increases.

[0016] In one specific embodiment, the mass ratio of Mg to (Si+Zn) is 0.1-1:1, specifically 0.1:1, 0.2:1, 0.3:1, 0.4:1, 0.5:1, 0.6:1, 0.7:1, 0.8:1, 0.9:1, or 1:1. Within this range, sufficient amounts of Mg2Si phase and MgZn2 reinforcing phase can be generated to improve the yield strength and tensile strength of the aluminum alloy.

[0017] In one specific embodiment, the mass ratio of Zn to Mg is 1-10:1, specifically 1, 1:1, 2:1, 3:1, 4:1, 5:1, 6:1, 7:1, 8:1, 9:1, or 10:1. Within this range, sufficient MgZn2 reinforcing phase can be generated to improve the yield strength and tensile strength of the aluminum alloy.

[0018] In one specific embodiment, the sum of the mass percentages of Si and Cu is 0.01-3% to ensure the strength of the aluminum alloy and to avoid the influence of Zn on the applied voltage during the anodizing of the alloy. Specifically, the sum of the mass percentages of Si and Cu can be 0.01%, 0.02%, 0.04%, 0.06%, 0.08%, 0.1%, 0.15%, 0.2%, 0.25%, 0.3%, 0.35%, 0.4%, 0.45%, 0.5%, 0.55%, 0.6%, 0.65%, 0.7%, 0.75%, 0.8%, 0.85%, 0.9%, 0.95%, 1%, 1.5%, 2%, 2.5%, or 3%.

[0019] In one specific embodiment, the mass ratio of Si to Fe is 1-20:1, specifically 1:1, 2:1, 3:1, 4:1, 5:1, 6:1, 7:1, 8:1, 9:1, 10:1, 11:1, 12:1, 13:1, 14:1, 15:1, 16:1, 17:1, 18:1, 19:1, or 20:1. As the mass ratio increases, the yield strength and tensile strength of the aluminum alloy gradually increase; conversely, they decrease.

[0020] In the technical solution of this invention, the anodizable Al-Zn-Mn-Mg die-cast aluminum alloy contains 2-4.5% Zn, 0.01-0.8% Si, 0.001-0.5% Fe, 0.001-0.3% Cu, 1-3% Mn, 0.8-4% Mg, 0-0.05% B, 0-0.05% Sn, 0-0.2% Sb, 0-0.1% In, and 0-0.5% Bi. The addition of Si, Fe, Cu, Mn, Mg, B, Sn, Sb, In, and Bi within the aforementioned content range, through mutual influence and interaction, can enhance the tensile strength, yield strength, and elongation (over 12%) of anodizable Al-Zn-Mn-Mg die-cast aluminum alloys. These alloys are also suitable for anodizing, producing anodized films with significant thickness, excellent transparency, gloss, and color uniformity, making them ideal for products with high aesthetic requirements, such as the mid-plates and frames of mobile devices like smartphones. Specifically: With the Mg content set at 0.8-4% by mass, Zn at 2-4.5% by mass, and Si at 0.01-0.8% by mass, sufficient Mg reacts with Zn and Si to form a large amount of MgZn2 strengthening phase and Mg2Si strengthening phase. A small amount of MgZn2 strengthening phase can significantly improve the alloy's strength without significantly affecting the elongation of the aluminum alloy. Simultaneously, the Mg2Si strengthening phase also improves the strength of the aluminum alloy and significantly reduces its elongation. Furthermore, the two strengthening phases can influence each other's precipitation behavior, significantly increasing the volume fraction of precipitated phases and reducing their average size. Finally, a certain amount of M is also present. Adding g (e.g., 0.1-0.8%) to the aluminum matrix improves the strength and elongation of the aluminum alloy. The addition of Zn and Si improves the fluidity of the aluminum alloy, ensuring its die-casting performance. The addition of Si also increases the anodizing voltage, preventing a decrease in the anodizing voltage caused by Zn addition. Setting the Si content to no more than 0.8% also prevents the anodized film from turning gray due to the presence of Si. Setting the Cu mass percentage content to 0.001-0.3% improves the strength of the aluminum alloy and promotes the precipitation of Mg2Si and MgZn2 strengthening phases, further enhancing the strength. The addition of Cu also improves the overall strength of the aluminum alloy. The applied voltage for gold anodizing should be adjusted to avoid the reduction in applied voltage caused by the addition of Zn. Setting the Fe mass percentage content to 0.001-0.5% improves the mold release performance of the aluminum alloy. Setting the Mn mass percentage content to 1-3% improves the mold release performance and prevents the formation of the AlFeSi phase (which consumes Si and reduces the Mg2Si phase content) when Fe content is too high. A higher Mn mass percentage content, such as greater than 1%, can promote the formation of the AlFeMnSi phase and reduce the formation of the AlFeSi phase. Most impurities in the alloy melt will also react with Mn and A. The reaction generates an Al-Mn-X phase (X being an impurity element). This phase can act as a nucleation point, increasing the nucleation rate to refine the grains and purify the aluminum alloy, thus significantly improving its elongation and strength. With a boron content of 0-0.05%, boron can react with transition metals (including Fe) to form compounds that can be separated from the molten alloy, such as ferroboron compounds, thus purifying the alloy. Boron readily adsorbs onto the surface of the iron-rich phase, inhibiting its growth and controlling its size. It also prevents the formation of the iron-rich phase in the molten alloy. Furthermore, boron refines the grains and the second phase, further improving the elongation of the aluminum alloy. The sn content is 0-0.At a mass percentage of 0.5%, Sn can react with Al, Fe, and Mg to form AlFeSn and Mg2Sn phases, thereby improving the yield strength and tensile strength of aluminum alloys. The formation of AlFeSn also prevents the formation of AlFeSi, which would consume Si and reduce the content of the Mg2Si phase. Sn can also adsorb onto the surface of the (CuMg)Al2 phase to prevent its growth, thus avoiding significant impact on the quality of the anodic oxide film. When the mass percentage of Sb is 0-0.2%, Sb will react with Al and Mg to form AlSb and Mg3Sb2 phases, thereby improving the yield strength and tensile strength of aluminum alloys. The concentration of In (In) at a mass percentage of 0-0.1% allows it to react with Al and Cu to form phases such as AlIn and CuIn, thereby improving the tensile strength and yield strength of aluminum alloys. In also refines the grain size, thus increasing the elongation of the aluminum alloy. Similarly, a Bi (Bi) concentration of 0-0.5% allows it to react with Al, Fe, and Mg to form phases such as Bi₂Mg₃ and Al₈Fe₂Bi, improving the yield strength and tensile strength of aluminum alloys. The formation of Al₈Fe₂Bi also prevents the formation of AlFeSi, which would otherwise consume Si and reduce the content of the Mg₂Si phase. Bi further refines the grain size and the second phase, thus increasing the elongation of the aluminum alloy.

[0021] The anodizable Al-Zn-Mn-Mg series aluminum alloy also contains 0.01-0.1% Ag, 0.01-0.3% Zr, and 0.01-0.3% RE by mass. RE is at least one of La, Ce, Pr, Nd, Er, Sm, Y, Gd, and Sc. When RE contains multiple elements, the mass percentage content of each rare earth element is 0.001-0.15%.

[0022] The specific mass percentage content of Ag can be 0.01%, 0.02%, 0.03%, 0.04%, 0.05%, 0.06%, 0.07%, 0.08%, 0.09%, or 0.1%. The specific mass percentage content of Zr and RE can be 0.01%, 0.02%, 0.04%, 0.06%, 0.08%, 0.1%, 0.11%, 0.12%, 0.13%, 0.14%, 0.15%, 0.16%, 0.17%, 0.18%, 0.19%, 0.2%, 0.21%, 0.22%, 0.23%, 0.24%, 0.25%, 0.26%, 0.27%, 0.28%, 0.29%, or 0.3%.

[0023] In Al-Zn-Mn-Mg alloys, the addition of Ag can alter the precipitation kinetics of the Mg2Si phase, promoting its precipitation and significantly improving the strength and elongation of the aluminum alloy. The added Zr can form an Al(RE,Zr) composite phase with RE. This Al(RE,Zr) composite phase provides dispersed nucleation sites for the Mg2Si phase, refining it. Furthermore, the Al(RE,Zr) composite phase optimizes the distribution of the Mg2Si phase, preventing the formation of coarse Mg2Si phase at grain boundaries and improving the uniformity of the anodic oxide film. Thus, the combined effect of Ag, Zr, and RE promotes the precipitation of the Mg2Si phase, optimizes its distribution, and refines it, thereby improving the strength and elongation of the aluminum alloy and enhancing its anodic oxidation performance, such as the uniformity of the anodic oxide film.

[0024] In one specific embodiment, RE represents Sc and Er, with Sc comprising 0.001-0.1% by mass and Er comprising 0.001-0.15% by mass. Specifically, the mass percentage of Sc can be 0.001%, 0.002%, 0.004%, 0.006%, 0.008%, 0.01%, 0.02%, 0.03%, 0.04%, 0.05%, 0.06%, 0.07%, 0.08%, 0.09%, or 0.1%. The mass percentage of Er can be 0.001%, 0.002%, 0.004%, 0.006%, 0.008%, 0.01%, 0.02%, 0.03%, 0.04%, 0.05%, 0.06%, 0.07%, 0.08%, 0.09%, 0.1%, 0.11%, 0.12%, 0.13%, 0.14%, or 0.15%. In Al-Zn-Mn-Mg alloys, the addition of Ag can alter the precipitation kinetics of the Mg2Si phase, promoting its precipitation and significantly improving the strength and elongation of the aluminum alloy. Zr can form Al3(Sc,Zr) and Al3(Er,Zr) composite phases with Sc and Er. The Al3(Sc,Zr) composite phase provides dispersed nucleation sites for the Mg2Si phase, refining it. The Al3(Er,Zr) composite phase also optimizes the distribution of the Mg2Si phase, preventing the formation of coarse Mg2Si phase at grain boundaries, thus improving the uniformity of the anodic oxide film. Therefore, the combined effect of Ag, Zr, Sc, and Er promotes the precipitation of the Mg2Si phase, optimizes its distribution, and refines it, thereby improving the strength and elongation of the aluminum alloy and enhancing its anodic oxidation properties, such as the uniformity of the anodic oxide film.

[0025] Anodizable Al-Zn-Mn-Mg series aluminum alloys also contain 0.001-0.2% Mo, 0.01-0.3% Zr, and 0.001-0.002% C by mass.

[0026] The specific percentage content of Mo by mass can be 0.001%, 0.002%, 0.004%, 0.006%, 0.008%, 0.01%, 0.02%, 0.04%, 0.06%, 0.08%, 0.1%, 0.11%, 0.12%, 0.13%, 0.14%, 0.15%, 0.16%, 0.17%, 0.18%, 0.19%, or 0.2%. The specific percentage content of Zr by mass can be 0.01%, 0.02%, 0.04%, 0.06%, 0.08%, 0.1%, 0.11%, 0.12%, 0.13%, 0.14%, 0.15%, 0.16%, 0.17%, 0.18%, 0.19%, 0.2%, 0.21%, 0.22%, 0.23%, 0.24%, 0.25%, 0.26%, 0.27%, 0.28%, 0.29%, or 0.3%. The specific percentage content of C by mass can be 0.001%, 0.0015%, or 0.002%.

[0027] In one embodiment, Zr and C can be added in the form of an Al5ZrC master alloy. In Al-Zn-Mn-Mg alloys, the addition of Zr can react with Al to form an Al3Zr dispersed phase. The Al3Zr dispersed phase can pin dislocations and act as heterogeneous nucleation sites for the Mg2Si phase, thereby refining the Mg2Si phase. The Al3Zr dispersed phase can also shorten the atomic diffusion path and accelerate the dispersed precipitation of the Mg2Si phase. C can shorten the atomic diffusion path and form a TiC phase with Ti. The TiC phase acts as a nucleation site, further accelerating the dispersed precipitation of the Mg2Si phase. Mo can lower the diffusion barrier of Zr and C and form an AlMo phase around the grain boundaries, promoting the dispersed and uniform distribution of Al3Zr particles. Therefore, when Zr and C are used in combination, they can effectively promote the dispersed precipitation of the Mg2Si phase.

[0028] The anodizable Al-Zn-Mn-Mg series aluminum alloys also contain 0.001-0.2% Mo, 0.01-0.3% Zr, and 0.001-0.3% V by mass, wherein the mass ratio of Mo, Zr, and V is 0.1-0.8:0.1-10:1.

[0029] The specific percentage content of Mo by mass can be 0.001%, 0.002%, 0.004%, 0.006%, 0.008%, 0.01%, 0.02%, 0.04%, 0.06%, 0.08%, 0.1%, 0.11%, 0.12%, 0.13%, 0.14%, 0.15%, 0.16%, 0.17%, 0.18%, 0.19%, or 0.2%. The specific percentage content of Zr by mass can be 0.01%, 0.02%, 0.04%, 0.06%, 0.08%, 0.1%, 0.11%, 0.12%, 0.13%, 0.14%, 0.15%, 0.16%, 0.17%, 0.18%, 0.19%, 0.2%, 0.21%, 0.22%, 0.23%, 0.24%, 0.25%, 0.26%, 0.27%, 0.28%, 0.29%, or 0.3%. The specific percentage content of V by mass can be 0.001%, 0.002%, 0.004%, 0.006%, 0.008%, 0.01%, 0.02%, 0.04%, 0.06%, 0.08%, 0.1%, 0.11%, 0.12%, 0.13%, 0.14%, 0.15%, 0.16%, 0.17%, 0.18%, 0.19%, 0.2%, 0.21%, 0.22%, 0.23%, 0.24%, 0.25%, 0.26%, 0.27%, 0.28%, 0.29%, or 0.3%.

[0030] The specific mass ratios of Mo, Zr, and V can be 0.1:0.1:1, 0.1:0.5:1, 0.1:1:1, 0.1:5:1, 0.1:10:1, 0.5:0.1:1, 0.5:0.5:1, 0.5:1:1, 0.5:5:1, 0.5:10:1, 0.8:0.1:1, 0.8:0.5:1, 0.8:1:1, 0.8:5:1, or 0.8:10:1.

[0031] In Al-Zn-Mn-Mg alloys, Zr can react with Al to form the Al3Zr dispersed phase. This Al3Zr dispersed phase can pin dislocations and act as heterogeneous nucleation sites for the Mg2Si phase, thus refining the Mg2Si phase. The Al3Zr dispersed phase can also shorten atomic diffusion paths, accelerating the dispersed precipitation of the Mg2Si phase. Mo can lower the diffusion barrier of Zr, promoting the uniform distribution of Al3Zr particles, thereby enabling Al3Zr to effectively promote the dispersed precipitation of the Mg2Si phase. V can react with Al to form Al at grain boundaries and within grains. 10 V-dispersed phase, especially Al within the crystal. 10 The dispersed V phase and the AlMo phase work together to pin dislocations, further refining the Mg2Si phase, avoiding coarsening, and further improving the strength and elongation of the aluminum alloy.

[0032] Anodizable Al-Zn-Mn-Mg aluminum alloys also contain 0-0.05% Li by mass, specifically 0.001%, 0.002%, 0.003%, 0.004%, 0.005%, 0.006%, 0.007%, 0.008%, 0.009%, 0.01%, 0.02%, 0.03%, 0.04%, or 0.05%. Li can react with Al and Mg to form Al3Li and Al2MgLi reinforcing phases, inhibiting recrystallization and producing ultrafine grains, thereby improving the density of the anodic oxide film. It can also reduce the density of the aluminum alloy, improve corrosion resistance, and reduce the porosity of the anodic oxide film.

[0033] Anodizable Al-Zn-Mn-Mg aluminum alloys also contain 0-0.3% Nb by mass, specifically 0.001%, 0.002%, 0.003%, 0.004%, 0.005%, 0.006%, 0.007%, 0.008%, 0.009%, 0.01%, 0.02%, 0.04%, 0.06%, 0.08%, 0.1%, 0.11%, 0.12%, 0.13%, 0.14%, 0.15%, 0.16%, 0.17%, 0.18%, 0.19%, 0.2%, 0.21%, 0.22%, 0.23%, 0.24%, 0.25%, 0.26%, 0.27%, 0.28%, 0.29%, or 0.3%. The melting point of Nb (2468℃) is 800℃ higher than that of Ti (1668℃), and the melting point of Al3Nb (1680℃) is 300℃ higher than that of Al3Ti (1350℃). This means that Nb-Al intermetallic compounds are more stable in the melt than Ti-Al intermetallic compounds. Furthermore, the lattice mismatch constant between NbB2 and Al (30.6%) is smaller than that between TiB2 and Al (34.0%). Considering only the interaction with Al, NbB2 is a more likely potential heterogeneous nucleation site than TiB2. In terms of crystal structure, Al3Nb and Al3Ti are identical, both having a coordination number of 8 and belonging to the tetragonal crystal system. In addition, Al3Nb and Al3Ti have the same lattice mismatch constant with Al. In summary, the physical, chemical, and crystallographic properties of NbB2 and Al3Nb particles in the Al-Nb-B master alloy suggest their potential as heterogeneous nucleation matrices.

[0034] Anodizable Al-Zn-Mn-Mg aluminum alloys also contain 0-0.5% Co by mass, specifically 0.001%, 0.002%, 0.004%, 0.006%, 0.008%, 0.01%, 0.02%, 0.04%, 0.06%, 0.08%, 0.1%, 0.15%, 0.2%, 0.25%, 0.3%, 0.35%, 0.4%, 0.45%, or 0.5%. The Co to Cr mass ratio can be set from 1 to 10:1, specifically 1:1, 2:1, 3:1, 4:1, 5:1, 6:1, 7:1, 8:1, 9:1, and 10:1. Co has low solubility in aluminum alloys, but it can form the AlCo phase with Al. The AlCo phase is dispersed in the aluminum alloy matrix, which can refine the grains and improve the anodizing and coloring characteristics of the aluminum alloy. Co, Al, and Cr together form a thermally stable Al-Co-Cr phase. This phase hinders dislocation movement and grain boundary migration, thus improving the strength of the aluminum alloy. The Co to Cr mass ratio can be set to 1-10:1 to ensure the quantity of the Al-Co-Cr phase and prevent it from becoming excessive. Furthermore, the aforementioned Al3(RE,Zr) phase can also prevent the aggregation of the Al-Co-Cr phase. Therefore, the combined use of Co, Cr, Zr, and RE yields even better results. In this case, the Zr mass percentage content can be 0.01-0.3%.

[0035] Anodizable Al-Zn-Mn-Mg alloys also contain 0.0001-0.2% Ca by mass, specifically 0.0001%, 0.0005%, 0.001%, 0.002%, 0.004%, 0.006%, 0.008%, 0.01%, 0.02%, 0.04%, 0.06%, 0.08%, 0.1%, 0.11%, 0.12%, 0.13%, 0.14%, 0.15%, 0.16%, 0.17%, 0.18%, 0.19%, or 0.2%. Ca can react with Al and Mn to form the Al6(Mn,Ca) phase. The Al6(Mn,Ca) phase inhibits the formation of the AlFeSi phase, preventing the consumption of Si and thus reducing the content of the Mg2Si phase. Ca can also react with Al and REs (such as La and Ce) to form the Al4CaCe and Al4CaLa phases. These phases refine grains, second phases, and precipitates, improving the strength and elongation of aluminum alloys and promoting the formation of a dense anodic oxide film. Furthermore, Ca can inhibit the coarsening of the TiAl3 phase, enhancing its grain-refining function and improving the uniformity and gloss of the anodic oxide film. Therefore, a relatively high mass percentage of Ca (up to 0.2%) can be set to allow Ca to react with Mn, REs, and Ti, thereby inhibiting the formation of the AlFeSi phase, refining grains, second phases, and precipitates, and suppressing the coarsening of the TiAl3 phase.

[0036] Anodizable Al-Zn-Mn-Mg aluminum alloys also contain 0-0.3% Cr by mass, specifically 0.001%, 0.002%, 0.004%, 0.006%, 0.008%, 0.01%, 0.02%, 0.04%, 0.06%, 0.08%, 0.1%, 0.15%, 0.2%, 0.25%, or 0.3%. Cr can refine the grains to improve the elongation of the aluminum alloy. Cr can also combine with Mn to improve the release properties, ensuring that the aluminum alloy still has good release properties even when the Fe content is low (e.g., less than 0.2%). Cr can also react with Al, Mn, and Fe to form the (FeMnCr)Al6 phase, which can prevent the formation of the AlFeSi phase from consuming Si and reducing the content of the Mg2Si phase.

[0037] Anodizable Al-Zn-Mn-Mg aluminum alloys also contain 0-0.2% Ni by mass, specifically 0.001%, 0.002%, 0.004%, 0.006%, 0.008%, 0.01%, 0.02%, 0.04%, 0.06%, 0.08%, 0.1%, 0.15%, or 0.2%. Ni can react with Al and Fe to form the AlNiFe reinforcing phase, thereby improving the strength of the aluminum alloy. Furthermore, by consuming Fe, the content of the AlFeSi phase can be reduced, increasing the content of the Mg2Si phase and further enhancing the strength of the aluminum alloy.

[0038] Anodizable Al-Zn-Mn-Mg aluminum alloys also contain 0-0.2% Ti by mass, specifically 0.001%, 0.002%, 0.004%, 0.006%, 0.008%, 0.01%, 0.02%, 0.04%, 0.06%, 0.08%, 0.1%, 0.15%, or 0.2%. Ti can react with Al to form the TiAl3 phase. The TiAl3 phase, as a heterogeneous nucleation site, can significantly refine the grains, second phase, and precipitated phases, thereby improving the elongation of the aluminum alloy.

[0039] Anodizable Al-Zn-Mn-Mg alloys also contain 0-0.5% Te by mass, specifically 0.001%, 0.002%, 0.004%, 0.006%, 0.008%, 0.01%, 0.02%, 0.04%, 0.06%, 0.08%, 0.1%, 0.15%, 0.2%, 0.25%, 0.3%, 0.35%, 0.4%, 0.45%, or 0.5%. The mass ratio of Sb to Te can be 0.1-10:1, specifically 0.1:1, 0.2:1, 0.3:1, 0.4:1, 0.5:1, 0.6:1, 0.7:1, 0.8:1, 0.9:1, 1:1, 2:1, 3:1, 4:1, 5:1, 6:1, 7:1, 8:1, 9:1, or 10:1. When Sb and Sr are added simultaneously, Sr can spheroidize the Mg3Sb2 phase, further improving the yield strength and tensile strength of the aluminum alloy. When Sb and Te are added simultaneously, the mass ratio of Sb to Te can be 0.1-10:1, which can form fine petal-shaped primary crystals to improve the tensile strength and elongation of the aluminum alloy.

[0040] Anodizable Al-Zn-Mn-Mg aluminum alloys also contain 0-0.05% Sr by mass, specifically 0.001%, 0.002%, 0.003%, 0.004%, 0.005%, 0.006%, 0.007%, 0.008%, 0.009%, 0.01%, 0.02%, 0.03%, 0.04%, or 0.05%. Sr preferentially combines with Fe to form dispersion strengthening, reducing the solid solubility of Fe, thereby improving the yield strength and tensile strength of the aluminum alloy. Crystallographically, Sr can alter the behavior of intermetallic compound phases and can act as a modifier, refining grains and the second phase through heterogeneous nucleation theory or twin valley mechanism to improve the elongation of the aluminum alloy and reduce the tendency of sticking during die casting.

[0041] Anodizable Al-Zn-Mn-Mg aluminum alloys also contain 0-0.1% Ge by mass, specifically 0.001%, 0.002%, 0.004%, 0.006%, 0.008%, 0.01%, 0.02%, 0.04%, 0.06%, 0.08%, or 0.1%. Ge can react with Al and Si to form second phases such as Al9Ge7, Al6Ge5, Al5Ge2, Al3Ge4, and SiGe; Ge can also promote the precipitation of second phases such as Mg2Si and CuAl2, thereby reducing the solid solubility of these elements in the aluminum matrix and improving the tensile strength and yield strength of the aluminum alloy; Ge can also refine the grains and second phases, thereby improving the elongation of the aluminum alloy.

[0042] Anodizable Al-Zn-Mn-Mg series aluminum alloys also contain 0-5% AlTiC, 0-5% AlTiB, 0-15% SiC, and 0-5% BN by mass percentage. The specific contents of AlTiC, AlTiB, and BN can be 0.001%, 0.005%, 0.01%, 0.05%, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2%, 2.1%, 2.2%, 2.3%, 2.4%, 2.5%, 2.6%, 2.7%, 2.8%, 2.9%, 3%, 3.1%, 3.2%, 3.3%, 3.4%, 3.5%, 3.6%, 3.7%, 3.8%, 3.9%, 4%, 4.1%, 4.2%, 4.3%, 4.4%, 4.5%, 4.6%, 4.7%, 4.8%, 4.9%, or 5%. The SiC content can be 0.001%, 0.005%, 0.01%, 0.05%, 0.1%, 0.5%, 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14%, or 15%.

[0043] When AlTiC, AlTiB, SiC, and BN are used in combination, the mass percentage content of AlTiC can be reduced to 0.1-1%, the mass percentage content of AlTiB can be reduced to 0.1-1%, the mass percentage content of SiC can be reduced to 0.1-6%, and the mass percentage content of BN can be reduced to 0.1-1%, thus reducing costs. AlTiB, SiC, AlTiC, and BN all have good refining effects; when used in combination, reducing the content of each individual component can achieve a better refining effect. AlTiB forms C-TiB2 particle complexes at the SiC-Al interface. The C atoms in SiC tend to enhance the adhesion energy of the C-TiB2 / Al interface, causing the originally elongated TiAl3 to break down and shorten, thus preventing the enrichment and growth of TiAl3 and greatly enhancing the composite grain refinement effect. BN disperses AlB2 and AlN nanonuclei at the aluminum matrix interface and grain boundaries, which can refine the grains and promote uniform grain nucleation to improve the elongation of the aluminum alloy. Under the action of SiC, Ti, B, and BN, AlTiC is not easy to aggregate and has a better grain refinement strengthening effect.

[0044] This invention also provides a method for preparing anodizable Al-Zn-Mn-Mg die-cast aluminum alloys, comprising the following steps: It provides Zn source, Si source, Fe source, Cu source, Mn source, Mg source, B source, Sn source, Sb source, In source, Bi source, and Al source; Aluminum liquid is obtained by heating an Al source at a temperature of 750-830°C; At a temperature of 720-780°C, Zn, Si, Fe, Cu, Mn, Mg, B, Sn, Sb, In, and Bi sources are added to molten aluminum to obtain an alloy liquid; and The alloy melt is refined, degassed, and formed to obtain an anodizable Al-Zn-Mn-Mg die-cast aluminum alloy. The anodizable Al-Zn-Mn-Mg die-cast aluminum alloy contains 2-4.5% Zn, 0.01-0.8% Si, 0.001-0.5% Fe, 0.001-0.3% Cu, 1-3% Mn, 0.8-4% Mg, 0-0.05% B, 0-0.05% Sn, 0-0.2% Sb, 0-0.1% In, and 0-0.5% Bi.

[0045] The Zn source, Si source, Fe source, Cu source, Mn source, Mg source, B source, Sn source, Sb source, In source, and Bi source can be elemental or intermediate alloy.

[0046] At least one of the following sources can be added to the molten aluminum: Ag, Zr, Mo, C, V, Li, Nb, Co, Ca, Sr, Ge, Cr, Ni, Ti, RE, AlTiC, AlTiB, BN, and SiC. These raw materials can also be added in elemental or intermediate alloy form.

[0047] The degassing process involves adjusting the temperature of the molten alloy to 650-780℃ and introducing an inert gas such as argon into the molten alloy using a degassing machine. Specific degassing temperatures can be 650℃, 660℃, 670℃, 680℃, 690℃, 700℃, 710℃, 720℃, 730℃, 740℃, 750℃, 760℃, 770℃, or 780℃. The degassing time is 10-30 minutes, specifically 10 minutes, 15 minutes, 20 minutes, 25 minutes, or 30 minutes.

[0048] The refining process involves introducing inert gases such as argon into the molten alloy using a degasser. A refining agent can be added simultaneously. The vortex created by the degasser's rotating disc in the molten alloy allows the refining agent to be evenly mixed into the alloy. The refining agent refines the alloy microstructure, improving the strength and elongation of the aluminum alloy. It has the advantages of good dispersibility and low cost. The refining time is 10-30 minutes, specifically 10, 15, 20, 25, or 30 minutes. The refining temperature is 650-780℃, specifically 650℃, 660℃, 670℃, 680℃, 690℃, 700℃, 710℃, 720℃, 730℃, 740℃, 750℃, 760℃, 770℃, or 780℃. The refining agent contains: 5-10 parts potassium fluoroaluminate, 6-20 parts AlTi5B1 metal powder, 8-25 parts potassium titanate whisker powder, 20-40 parts sodium chloride + potassium chloride, 5-10 parts potassium nitrate, 5-10 parts potassium carbonate, and 0.5-3 parts potassium silicate.

[0049] The parting surface of the mold can undergo surface treatment to form a boron carbide layer. This layer not only improves demolding performance but also enhances the mold's wear resistance and protects against corrosion from acids, alkalis, salts, and other chemicals, as well as thermal erosion of aluminum alloys, thus extending the mold's service life. The thickness of the boron carbide layer can range from 1 to 10 mm, specifically 1 mm, 2 mm, 3 mm, 4 mm, 5 mm, 6 mm, 7 mm, 8 mm, 9 mm, or 10 mm. The surface treatment can involve mixing a boron-containing gas (such as BCl3) with a carbon-containing gas (such as CH4) to obtain a mixed gas. This mixed gas is then introduced into the cavity, and through chemical vapor deposition (CVD), the boron-containing and carbon-containing gases react chemically and deposit onto the parting surface to form the boron carbide layer. The CVD temperature is 900-1200°C, the deposition pressure is 200-500 Pa, and the carrier gas flow rate is 100-200 sccm. The boron carbide layer can increase the hardness of mold steel to 3000-4000 Hv; the boron carbide layer can reduce the affinity of the mixed melt to the mold surface, improve the demolding performance of aluminum alloy, and greatly increase the elongation of aluminum alloy; the boron carbide layer can resist the corrosion of chemicals such as acids, alkalis, and salts, and can improve the corrosion resistance of aluminum alloy; the boron carbide layer can maintain good physical and chemical properties at high temperature, and can improve the thermal stability of aluminum alloy; the boron carbide layer has an extremely low coefficient of friction, improves the surface smoothness of aluminum alloy, and can significantly reduce the wear and energy consumption of aluminum alloy products caused by mechanical friction; the boron carbide layer also has high heat transfer properties. During the instant of aluminum alloy forming, the boron carbide layer can quickly conduct away heat, increasing the heat transfer rate of the mold by 2-4 times that of ordinary molds, allowing the aluminum alloy to cool down faster.

[0050] In one embodiment, the forming process includes: die casting the alloy liquid at a temperature of 640-700ºC (i.e., conventional die casting), wherein the die casting speed of the die casting machine is 0.23-2.5 m / s. During the die casting process, the temperature cooling rate is 50-150 K / s, specifically 50 K / s, 60 K / s, 70 K / s, 80 K / s, 90 K / s, 100 K / s, 110 K / s, 120 K / s, 130 K / s, 140 K / s, or 150 K / s. During the die casting process, a temperature cooling rate of 50-150 K / s can suppress the formation of the Mg5Al8 phase. Generally, when the Fe content exceeds 0.2%, the AlFeSi phase is formed. The AlFeSi phase affects the strength of the aluminum alloy and also the transparency, gloss, and color uniformity of the anodic oxide film. In this invention, the cooling rate is set to 50-150 K / s during the die-casting process, which suppresses the formation of the AlFeSi phase, resulting in only a small amount of dispersed AlFe phase. This AlFe phase improves the strength of the aluminum alloy without affecting the transparency, gloss, or color uniformity of the anodic oxide film. Thus, even with a Mg content of 5.5% and an Fe content of 0.5%, the adverse effects of excessive Mg and Fe can be avoided.

[0051] In another embodiment, the forming process includes: vacuum die casting of the alloy liquid at a temperature of 640-700°C, wherein the vacuum degree is 30-50 mbar, the injection speed is 2-5 m / s, and the casting pressure is 80-120 MPa. It is understood that vacuum die casting can significantly reduce the porosity of aluminum alloy castings and increase their density, resulting in higher strength (e.g., yield strength and tensile strength) and elongation of the vacuum-die-cast aluminum alloy compared to that of the aluminum alloy treated with conventional die casting. During vacuum die casting, the cooling rate is 100-200 K / s, specifically 100 K / s, 110 K / s, 120 K / s, 130 K / s, 140 K / s, 150 K / s, 160 K / s, 170 K / s, 180 K / s, 190 K / s, or 2000 K / s. A cooling rate of 100-200 K / s during vacuum die casting can suppress the formation of the Mg5Al8 phase. Generally, when the Fe content exceeds 0.2%, the AlFeSi phase will form. The AlFeSi phase affects the strength of the aluminum alloy and also the transparency, gloss, and color uniformity of the anodic oxide film. In this invention, the cooling rate is set to 100-200 K / s during the vacuum die-casting process, which avoids the formation of the AlFeSi phase, resulting only in a small amount of dispersed AlFe phase. The AlFe phase can improve the strength of the aluminum alloy without affecting the transparency, gloss, and color uniformity of the anodic oxide film. Thus, even if the Mg content reaches 5.5% and the Fe content reaches 0.5%, the adverse effects of excessive Mg and Fe can still be avoided.

[0052] Understandably, even with cooling treatment, die casting, and vacuum die casting processes, small amounts of Mg5Al8 and AlFeSi phases will still exist.

[0053] In another embodiment, the forming process includes the following steps: molten alloy is pushed into a mold and subjected to low-pressure filling casting. Once the molten alloy enters the semi-solid solidification zone, a semi-solid aluminum alloy part is formed. The semi-solid aluminum alloy part is then subjected to in-situ primary forging and in-situ secondary forging pre-deformation treatments within the mold to obtain the aluminum alloy part. The deformation amount of the semi-solid aluminum alloy part in the in-situ primary forging treatment is 5-50%, and the deformation amount in the in-situ secondary forging treatment is 2-20%. The aluminum alloy part is then heat-treated to obtain an anodizable Al-Zn-Mn-Mg series aluminum alloy. The deformation amount of the semi-solid aluminum alloy part in the in-situ primary forging treatment is greater than that in the in-situ secondary forging treatment.

[0054] In low-pressure filling casting, the filling speed (i.e., the moving speed of the punch) is 0.1-1.2 m / s, the filling time (i.e., the time required for the molten alloy to completely fill the mold) is 2-20 s, the casting pressure is 0.1-40 MPa, the holding time is 2-10 s (i.e., the time to hold the molten alloy under a certain pressure after it has completely filled the mold), the mold temperature is 180-350℃, and the alloy casting temperature (i.e., the temperature when the molten alloy is filled into the mold) is 620-720℃.

[0055] A filling speed of 0.1-1.2 m / s increases the fluidity of the molten alloy, facilitating its full filling of the cavity. At this speed, the pressure applied by the punch to the molten alloy is also relatively low (specific pressure approximately 50-200 MPa), preventing casting defects such as porosity, shrinkage cavities, and looseness in the aluminum alloy product. It also avoids splashing and turbulence caused by excessively fast filling speeds, which can lead to casting defects such as oxide inclusions and air entrapment. Specific filling speeds can be 0.1 m / s, 0.2 m / s, 0.3 m / s, 0.4 m / s, 0.5 m / s, 0.6 m / s, 0.7 m / s, 0.8 m / s, 0.9 m / s, 1 m / s, 1.05 m / s, 1.1 m / s, 1.15 m / s, or 1.2 m / s. Specific filling times can be 2 s, 5 s, 10 s, 15 s, or 20 s.

[0056] Under casting pressures ranging from 0.1 to 40 MPa, the molten alloy is relatively stable and can solidify sequentially in a directional manner. The precipitates (both continuous and discontinuous) within the semi-solid aluminum alloy parts are perpendicular to the basal surface of the aluminum alloy matrix. When the molten alloy solidifies smoothly, there are fewer pores, loose areas, and cracks in the semi-solid aluminum alloy parts. Specific casting pressures can be 0.1 MPa, 0.5 MPa, 1 MPa, 5 MPa, 10 MPa, 15 MPa, 20 MPa, 25 MPa, 30 MPa, 35 MPa, or 40 MPa.

[0057] Semi-solid aluminum alloy parts can be formed within a holding time of 2-10 seconds and a casting pressure of 0.1-40 MPa. As the holding time and casting pressure increase, the casting microstructure within the semi-solid aluminum alloy parts gradually becomes more uniform and dense. After 10 seconds or if the casting pressure is too high, the liquid phase within the mold completely solidifies, preventing the formation of semi-solid aluminum alloy parts. Specific holding times can be 2s, 3s, 4s, 5s, 6s, 7s, 8s, 9s, or 10s.

[0058] The low-pressure filling casting process of this invention requires lower casting and mold preheating temperatures, which not only reduces thermal shock corrosion to the mold but also saves energy. The mold temperature can specifically be 180°C, 200°C, 250°C, 300°C, or 350°C. The alloy casting temperature can specifically be 620°C, 630°C, 640°C, 650°C, 660°C, 670°C, 680°C, 690°C, 700°C, 710°C, or 720°C.

[0059] In semi-solid aluminum alloy parts, the solid-liquid ratio, or solid phase fraction, is 20-90%, specifically 20%, 25%, 30%, 35%, 40%, 45%, 50%, 55%, 60%, 65%, 70%, 75%, 80%, 85%, or 90%. At this solid-liquid ratio, there are fewer casting defects in semi-solid aluminum alloy parts, and the precipitated phases within them solidify almost entirely vertically.

[0060] In the in-situ primary forging process, the forging temperature (i.e., the temperature of the semi-solid aluminum alloy parts in the mold) is 430-610℃, the forging specific pressure is 50-300MPa, the forging start time (i.e., the time interval between the formation of the semi-solid aluminum alloy parts and the in-situ primary forging process) is 2-20s, the holding time is 2-20s, and the deformation is 5-50%. After this in-situ primary forging process, the semi-solid aluminum alloy parts are transformed into solid parts.

[0061] The forging temperature can be 430℃, 440℃, 450℃, 460℃, 470℃, 480℃, 490℃, 500℃, 510℃, 520℃, 530℃, 540℃, 550℃, 560℃, 570℃, 580℃, 590℃, 600℃, or 610℃. The forging pressure can be 50MPa, 60MPa, 70MPa, 80MPa, 90MPa, 100MPa, 120MPa, 140MPa, 160MPa, 180MPa, 200MPa, 220MPa, 240MPa, 260MPa, 280MPa, or 300MPa. The specific forging start time can be 2s, 3s, 4s, 5s, 6s, 7s, 8s, 9s, 10s, 11s, 12s, 13s, 14s, 15s, 16s, 17s, 18s, 19s, or 20s. The specific pressure holding time can be 2s, 3s, 4s, 5s, 6s, 7s, 8s, 9s, 10s, 11s, 12s, 13s, 14s, 15s, 16s, 17s, 18s, 19s, or 20s.

[0062] With a deformation amount of 5-50%, semi-solid aluminum alloy parts can be transformed into solid aluminum alloy parts after in-situ primary forging. In these solid aluminum alloy parts, the volume fraction of continuous precipitates is significantly greater than that of discontinuous precipitates. As the deformation amount increases, the volume fraction of continuous precipitates gradually increases, thereby improving the mechanical properties of the aluminum alloy (including yield strength, tensile strength, and elongation). The preferred deformation amount is 20-30%, with both continuous and discontinuous precipitates being essentially perpendicular to the basal plane, significantly improving the alloy's mechanical properties (including yield strength, tensile strength, and elongation). Specific deformation amounts can be 5%, 6%, 7%, 8%, 9%, 10%, 12%, 14%, 16%, 18%, 20%, 22%, 24%, 26%, 28%, 30%, 32%, 34%, 36%, 38%, 40%, 42%, 44%, 46%, 48%, or 50%.

[0063] In this in-situ primary forging process, the semi-solid aluminum alloy parts are not cooled, removed from the mold, and then placed in the forging device for reheating to the forging temperature. Instead, the semi-solid aluminum alloy parts are directly subjected to in-situ primary forging in the original mold, without the need for cooling and reheating. This allows the solid-liquid mixed phases present in the semi-solid aluminum alloy parts to deform and solidify uniformly in this in-situ primary forging process on the basis of low-pressure filling casting (without cooling to around room temperature before reheating and forging, the deformation during cooling and heating is uncontrollable and it is difficult to maintain the semi-solid state). This further eliminates casting defects in the semi-solid aluminum alloy parts, significantly refines the coarse grains and the as-cast structure of the second phase, refines the size of continuous and discontinuous precipitates, and produces a large number of nanoscale precipitates inside the grains. The competition between discontinuous and continuous precipitates is accelerated, the continuous precipitates suppress the discontinuous precipitates, the volume fraction of continuous precipitates increases, and the volume fraction of discontinuous precipitates decreases, thereby improving the mechanical properties of the alloy.

[0064] To improve the smooth transition between low-pressure filling casting and in-situ primary forging, a first cooling process is performed during low-pressure filling casting. This ensures that semi-solid aluminum alloy parts with a temperature of 430-610℃ are obtained immediately after pressure holding, allowing for faster entry into the in-situ primary forging process. Alternatively, if the first cooling process during low-pressure filling casting does not result in a semi-solid aluminum alloy part with a solid content of 20-90% after pressure holding (e.g., the solid content is below 20%), a semi-solid aluminum alloy part with a temperature of 430-610℃ (solid content of 20-90%) can be obtained by undergoing a forging start-up time. Or, a second cooling process during the forging start-up time and in-situ primary forging can achieve a semi-solid aluminum alloy part with a temperature of 430-610℃ (solid content of 20-90%). A circulating oil circuit, such as a 3D contour cooling circuit, can be configured for cooling and temperature control.

[0065] In the low-pressure filling casting process, the temperature cooling rate of the first cooling treatment is 1-50℃ / s, specifically 1℃ / s, 5℃ / s, 10℃ / s, 15℃ / s, 20℃ / s, 25℃ / s, 30℃ / s, 35℃ / s, 40℃ / s, 45℃ / s, or 50℃ / s.

[0066] In the in-situ primary forging process, the temperature cooling rate for the second cooling step is 5-60℃ / s, specifically 5℃ / s, 10℃ / s, 15℃ / s, 20℃ / s, 25℃ / s, 30℃ / s, 35℃ / s, 40℃ / s, 45℃ / s, 50℃ / s, 55℃ / s, or 60℃ / s.

[0067] In in-situ two-stage forging pre-deformation treatment, the forging temperature is 250-420℃, the forging specific pressure is 50-500MPa, the holding time is 0-10s, and the deformation is 2-20%. The deformation of semi-solid aluminum alloy parts in in-situ one-stage forging treatment is greater than that of solid aluminum alloy parts in in-situ two-stage forging pre-deformation treatment. The deformation of semi-solid aluminum alloy parts in in-situ one-stage forging treatment is 2.5-25 times that of solid aluminum alloy parts in in-situ two-stage forging pre-deformation treatment.

[0068] The specific forging temperature can be 250℃, 260℃, 270℃, 280℃, 290℃, 300℃, 310℃, 320℃, 330℃, 340℃, 350℃, 360℃, 370℃, 380℃, 390℃, 400℃, 410℃, or 420℃. Temperatures below 250℃ can cause aluminum alloy parts to fracture, while temperatures above 430℃ can easily lead to complete recrystallization, resulting in excessively large grain and precipitated phase sizes, which is also unfavorable for twin formation and leads to a decrease in mechanical properties.

[0069] The forging specific pressure can be 50 MPa, 60 MPa, 70 MPa, 80 MPa, 90 MPa, 100 MPa, 120 MPa, 140 MPa, 160 MPa, 180 MPa, 200 MPa, 220 MPa, 240 MPa, 260 MPa, 280 MPa, 300 MPa, 320 MPa, 340 MPa, 360 MPa, 380 MPa, 400 MPa, 420 MPa, 440 MPa, 460 MPa, 480 MPa, or 500 MPa. The forging specific pressure in the in-situ secondary forging pre-deformation treatment is preferably greater than the forging specific pressure in the in-situ primary forging treatment to further promote the refinement of the continuous precipitate size. In one embodiment, the forging specific pressure of the in-situ secondary forging pre-deformation treatment is 1.5-5 times that of the forging specific pressure in the in-situ primary forging treatment, specifically 1.5 times, 2 times, 2.5 times, 3 times, 3.5 times, 4 times, 4.5 times, or 5 times.

[0070] The holding time can be 0s, 1s, 2s, 3s, 4s, 5s, 6s, 7s, 8s, 9s, or 10s. For example, after in-situ primary forging, when the parameter requirements of in-situ secondary forging pre-deformation are met, the pressure can be held for a certain period of time (e.g., 2s). For example, when the parameters reach the in-situ secondary forging pre-deformation, the in-situ secondary forging pre-deformation can be stopped immediately, and subsequent heat treatment can be carried out. This holding time can be 0s. For example, when the parameters reach the in-situ secondary forging pre-deformation, the pressure can be held for 5s before subsequent heat treatment.

[0071] The deformation amount can be 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14%, 15%, 16%, 17%, 18%, 19%, or 20%.

[0072] The deformation amount in the in-situ primary forging process is 2.5 times, 3 times, 4 times, 5 times, 6 times, 7 times, 8 times, 9 times, 10 times, 11 times, 12 times, 13 times, 14 times, 15 times, 16 times, 17 times, 18 times, 19 times, 20 times, 21 times, 22 times, 23 times, 24 times, or 25 times that in the in-situ secondary forging pre-deformation process. This process can effectively eliminate casting defects in semi-solid aluminum alloy parts and initially refine the grains and second-phase as-cast structure, resulting in a large number of nanoscale precipitates within the grains. The subsequent in-situ secondary forging pre-deformation process further refines these continuous precipitates, thus yielding an aluminum alloy with excellent mechanical properties.

[0073] Understandably, the mold is an integrated casting and forging mold, where the punch, driven by a feed rod, pushes the mixture into the mold cavity for casting and forging. During low-pressure filling casting, the filling speed and time can be adjusted by regulating the punch speed. The downward pressure of the punch during filling generates injection force, and the stroke of the punch after filling generates additional pressure. This injection force and additional pressure can be used to regulate the casting pressure during the casting process. Similarly, in subsequent in-situ primary forging and secondary forging pre-deformation processes, the forging pressure can also be adjusted by regulating the punch stroke.

[0074] To improve the smoothness of the connection between the in-situ primary forging process and the in-situ secondary forging pre-deformation process, a second cooling process was carried out during the in-situ primary forging process. This allows solid aluminum alloy parts with a temperature of 250-450℃ to be obtained as soon as possible after the pressure holding is completed, so that they can enter the in-situ secondary forging pre-deformation process as soon as possible.

[0075] The high dislocation density generated by the pre-formed twins through in-situ secondary forging pre-deformation treatment provides more diffusion pathways for the dissolution of Mg, Zn, Si, Cu, and Mn solute atoms in the aluminum matrix, accelerates aging kinetics and promotes the nucleation of precipitates, accelerates the formation of continuous precipitates during aging, enhances the age hardening response of the alloy, and further refines the grain size.

[0076] A third cooling process was performed during the in-situ secondary forging pre-deformation treatment to facilitate the formation of twins. The cooling rate for this third cooling process in the in-situ secondary forging pre-deformation treatment was 20-60℃ / s, specifically 20℃ / s, 25℃ / s, 30℃ / s, 35℃ / s, 40℃ / s, 45℃ / s, 50℃ / s, 55℃ / s, or 60℃ / s. Cooling treatment was performed during the low-pressure filled casting, in-situ primary forging, and in-situ secondary forging pre-deformation processes. After these three processes (low-pressure filled casting, in-situ primary forging, and in-situ secondary forging pre-deformation), the aluminum alloy of this invention essentially lacks the Mg5Al8 phase, and the amount of the AlFeSi phase is also relatively small. Even if the mass percentage of Mg reaches 5.5%, the Mg5Al8 phase will not form, thus reducing the film formation efficiency, the thickness of the anodic oxide film, and the uniformity and gloss of the anodic oxide film. Even if the Fe content reaches 0.5%, the formation of the AlFeSi phase can be suppressed, thus avoiding the AlFeSi phase from affecting the strength of the aluminum alloy and the transparency, gloss and color uniformity of the anodic oxide film.

[0077] In one embodiment, the heat treatment includes aging treatment, in which the temperature is 90-140°C, specifically 90°C, 100°C, 110°C, 120°C, 130°C, or 140°C, and the time is 10-200 hours, specifically 10 hours, 20 hours, 30 hours, 40 hours, 50 hours, 60 hours, 70 hours, 80 hours, 90 hours, 100 hours, 110 hours, 120 hours, 130 hours, 140 hours, 150 hours, 160 hours, 170 hours, 180 hours, 190 hours, or 200 hours.

[0078] In another embodiment, the heat treatment includes solution treatment and aging treatment. In the solution treatment, the temperature is 400-470℃, specifically 400℃, 410℃, 420℃, 430℃, 440℃, 450℃, 460℃, or 470℃, and the time is 10-50 hours, specifically 10 hours, 20 hours, 30 hours, 40 hours, or 50 hours. In the aging treatment, the temperature is 90-140℃. The temperature can be 90℃, 100℃, 110℃, 120℃, 130℃, or 140℃, and the time can be 10-200h, specifically 10h, 20h, 30h, 40h, 50h, 60h, 70h, 80h, 90h, 100h, 110h, 120h, 130h, 140h, 150h, 160h, 170h, 180h, 190h, or 200h.

[0079] During solution treatment, the solute atoms diffuse uniformly, dissolving coarse second phases (such as Mg2Si, MgZn2, AlFeSi, and Mg5Al8 phases, if present) and increasing the solid solubility of alloying elements in the aluminum matrix, creating conditions for subsequent aging treatment. During aging heat treatment, new precipitates formed along the prismatic or pyramidal surfaces grow uniformly and diffusely along their original orientation. These precipitates, perpendicular to the basal plane of the alloy matrix, significantly improve the alloy's yield strength, tensile strength, and elongation. Thus, in-situ primary forging can eliminate casting defects in the semi-solid alloy formed during low-pressure filled casting and refine the alloy. In in-situ secondary forging pre-deformation, pre-formed twins intensify the vertical precipitation of more continuous precipitates. In solution treatment, the solid solubility further increases, and in subsequent aging treatment, the precipitates gradually grow. By combining low-pressure filling casting, in-situ primary forging, in-situ secondary forging pre-deformation, and heat treatment, an aluminum alloy product with excellent comprehensive properties (including yield strength, tensile strength, and elongation) is obtained, and the aluminum alloy product can have complex shapes.

[0080] In this invention, an alloy liquid containing Zn, Si, Fe, Cu, Mn, Mg, B, Sn, Sb, In, and Bi elements is refined, degassed, and formed to obtain an anodizable Al-Zn-Mn-Mg aluminum alloy. The combined addition of Zn, Si, Fe, Cu, Mn, Mg, B, Sn, Sb, In, and Bi within the aforementioned content range, through mutual influence and interaction, results in an anodizable Al-Zn-Mn-Mg aluminum alloy with a tensile strength greater than 310 MPa, a yield strength greater than 170 MPa, and an elongation greater than 12%. This anodizable Al-Zn-Mn-Mg aluminum alloy is also suitable for anodizing, producing an anodized film with not only significant thickness but also excellent transparency, gloss, and color uniformity. This makes the anodizable Al-Zn-Mn-Mg aluminum alloy suitable for manufacturing structural components with high aesthetic requirements, such as the mid-plate and mid-frame of mobile devices like smartphones. The alloy liquid may further contain at least one of Ag, Zr, Mo, C, V, Li, Nb, Co, Ca, Sr, Ge, Cr, Ni, Ti, Te, RE, AlTiC, AlTiB, BN, and SiC.

[0081] During the forming process, the molten alloy is pushed into the mold by a punch for low-pressure filling casting. Once the molten alloy enters the semi-solid solidification zone, the semi-solid aluminum alloy part undergoes in-situ first-stage forging with large deformation and in-situ second-stage forging pre-deformation treatment within the mold to obtain the aluminum alloy part. The aluminum alloy part is then heat-treated to obtain the aluminum alloy product. This aluminum alloy product not only possesses the structural complexity of cast products but also the high strength and toughness of deformed products. The method eliminates the need to remove the semi-solid aluminum alloy part from the low-pressure filling casting mold and place it into the mold for subsequent multi-stage forging, giving the aluminum alloy preparation method of this invention advantages such as fewer process steps, shorter production cycle, higher production efficiency, and lower cost. During the low-pressure filling casting process, casting defects inside the aluminum alloy part are minimal. During the in-situ first-stage forging process with large deformation, casting defects inside semi-solid aluminum alloy parts are further eliminated, and the coarse grains and second-phase as-cast structure are significantly refined. A large number of nanoscale precipitates appear inside the grains, and the size of continuous and discontinuous precipitates is refined. The competition between discontinuous and continuous precipitates is accelerated, and continuous precipitates suppress discontinuous precipitates. The volume fraction of continuous precipitates increases, while the volume fraction of discontinuous precipitates decreases, thereby improving the mechanical properties of the alloy (including yield strength, tensile strength, and elongation). During the in-situ secondary forging pre-deformation process, the grain size can be further refined. The high-density dislocation density generated by the pre-formed twins provides more diffusion pathways for the dissolution of Mg, Zn, Si, Cu, and Mn solute atoms in the aluminum matrix during subsequent heat treatment. This accelerates aging kinetics and promotes the nucleation of precipitates, enhances the age hardening response of the alloy, accelerates the formation of continuous precipitates during aging, and further increases the volume fraction of continuous precipitates, thereby improving the mechanical properties of the alloy.

[0082] This invention also provides an aluminum alloy structural component, at least a portion of which is made of an anodizable Al-Zn-Mn-Mg aluminum alloy or an anodizable Al-Zn-Mn-Mg aluminum alloy prepared by a specific method. This aluminum alloy structural component can be used to manufacture the housing of mobile devices, such as the middle plate and frame of a mobile phone housing. The surface of the aluminum alloy structural component can be anodized to form an anodized film. The thickness of the anodized film can be 10-500 mm, and can be adjusted according to actual needs.

[0083] Example Please refer to Table 1 for the composition and content of the anodizable Al-Zn-Mn-Mg die-cast aluminum alloys in Examples 1 to 14, and please refer to Table 2 for the performance test results.

[0084] Table 1. Composition and content of aluminum alloys in Examples 1 to 14 For the sake of simplicity, the content of trace elements such as impurities in the comparative examples and embodiments is not shown.

[0085] When preparing the aluminum alloys of Examples 1 to 14, the preparation methods of these aluminum alloys differ in the types and contents of elements, as well as in the forming process. Other steps, such as Al source heating temperature, refining process, and degassing process, can be the same.

[0086] When preparing the anodizable Al-Zn-Mn-Mg series cast-forged aluminum alloy of Example 1, the forming process includes low-pressure filling casting forming process, in-situ first-stage forging process, in-situ second-stage forging pre-deformation process, and aging process.

[0087] In the low-pressure filling casting process, the filling speed is 0.1 m / s, the filling time is 20 s, the casting pressure is 0.1 MPa, the holding time is 2 s, the mold temperature is 200℃, the alloy casting temperature is 660℃, and the cooling rate is 20℃ / s. In the in-situ primary forging process, the forging temperature is 420℃, the forging specific pressure is 50 MPa, the forging start time is 20 s, the holding time is 2 s, the cooling rate is 10℃ / s, and the deformation is 10%. In the in-situ secondary forging pre-deformation process, the forging temperature is 420℃, the forging specific pressure is 100 MPa, the holding time is 10 s, the cooling rate is 32℃ / s, and the deformation is 3%. In the aging treatment, the temperature is 100℃, and the time is 30 h.

[0088] When preparing the anodizable Al-Zn-Mn-Mg series cast-forged aluminum alloy of Example 2, the forming process includes low-pressure filled casting forming process, in-situ first-stage forging process, in-situ second-stage forging pre-deformation process, and aging process.

[0089] In the low-pressure filling casting process, the filling speed is 0.1 m / s, the filling time is 20 s, the casting pressure is 0.1 MPa, the holding time is 2 s, the mold temperature is 200℃, the alloy casting temperature is 660℃, and the cooling rate is 5℃ / s. In the in-situ primary forging process, the forging temperature is 550℃, the forging specific pressure is 300 MPa, the forging start time is 10 s, the holding time is 20 s, the cooling rate is 10℃ / s, and the deformation is 50%. In the in-situ secondary forging pre-deformation process, the forging temperature is 350℃, the forging specific pressure is 100 MPa, the holding time is 10 s, the cooling rate is 21℃ / s, and the deformation is 4%. In the aging treatment, the temperature is 140℃, and the time is 5 h.

[0090] When preparing the anodizable Al-Zn-Mn-Mg series cast-forged aluminum alloy of Example 3, the forming process includes low-pressure filled casting forming process, in-situ first-stage forging process, in-situ second-stage forging pre-deformation process, and solution treatment.

[0091] In the low-pressure filling casting process, the filling speed is 0.5 m / s, the filling time is 10 s, the casting pressure is 40 MPa, the holding time is 5 s, the mold temperature is 260℃, the alloy casting temperature is 650℃, and the cooling rate is 10℃ / s. In the in-situ primary forging process, the forging temperature is 500℃, the forging specific pressure is 300 MPa, the forging start time is 2 s, the holding time is 4 s, the cooling rate is 50℃ / s, and the deformation is 49%. In the in-situ secondary forging pre-deformation process, the forging temperature is 300℃, the forging specific pressure is 60 MPa, the holding time is 1 s, the cooling rate is 20℃ / s, and the deformation is 5%. In the solution treatment, the temperature is 470℃ for 20 h, and in the aging treatment, the temperature is 120℃ for 60 h.

[0092] When preparing the anodizable Al-Zn-Mn-Mg series cast-forged aluminum alloy of Example 4, the forming process includes low-pressure filled casting forming process, in-situ first-stage forging process, in-situ second-stage forging pre-deformation process, and solution treatment.

[0093] In the low-pressure filling casting process, the filling speed is 0.5 m / s, the filling time is 10 s, the casting pressure is 40 MPa, the holding time is 5 s, the mold temperature is 260℃, the alloy casting temperature is 650℃, and the cooling rate is 10℃ / s. In the in-situ primary forging process, the forging temperature is 500℃, the forging specific pressure is 300 MPa, the forging start time is 4 s, the holding time is 4 s, the cooling rate is 25℃ / s, and the deformation is 49%. In the in-situ secondary forging pre-deformation process, the forging temperature is 300℃, the forging specific pressure is 100 MPa, the holding time is 1 s, the cooling rate is 20℃ / s, and the deformation is 15%. In the solution treatment, the temperature is 400℃ and the time is 20 h. In the aging treatment, the temperature is 110℃ and the time is 30 h.

[0094] When preparing the anodizable Al-Zn-Mn-Mg series cast-forged aluminum alloy of Example 5, the forming process includes low-pressure filled casting forming process, in-situ first-stage forging process, in-situ second-stage forging pre-deformation process, solution treatment and aging treatment.

[0095] In the low-pressure filling casting process, the filling speed is 1.2 m / s, the filling time is 2 s, the casting pressure is 1 MPa, the holding time is 2 s, the mold temperature is 350℃, the alloy casting temperature is 720℃, and the temperature cooling rate is 10℃ / s. In the in-situ primary forging process, the forging temperature is 610℃, the forging specific pressure is 100 MPa, the forging start time is 1 s, the holding time is 7 s, the temperature cooling rate is 30℃ / s, and the deformation is 20%. In the in-situ secondary forging pre-deformation process, the forging temperature is 400℃, the forging specific pressure is 120 MPa, the holding time is 1 s, the temperature cooling rate is 20℃ / s, and the deformation is 6%. In the solution treatment, the temperature is 400℃ and the time is 50 h. In the aging treatment, the temperature is 90℃ and the time is 150 h.

[0096] When preparing the anodizable Al-Zn-Mn-Mg series cast-forged aluminum alloy of Example 6, the forming process includes low-pressure filled casting forming process, in-situ first-stage forging process, in-situ second-stage forging pre-deformation process, solution treatment and aging treatment.

[0097] In the low-pressure filling casting process, the filling speed is 1.2 m / s, the filling time is 2 s, the casting pressure is 1 MPa, the holding time is 2 s, the mold temperature is 350℃, the alloy casting temperature is 700℃, and the cooling rate is 30℃ / s. In the in-situ primary forging process, the forging temperature is 600℃, the forging specific pressure is 150 MPa, the forging start time is 2 s, the holding time is 12 s, the cooling rate is 20℃ / s, and the deformation is 25%. In the in-situ secondary forging pre-deformation process, the forging temperature is 360℃, the forging specific pressure is 150 MPa, the holding time is 1 s, the cooling rate is 20℃ / s, and the deformation is 8%. In the solution treatment, the temperature is 470℃ for 10 h, and in the aging treatment, the temperature is 120℃ for 100 h.

[0098] When preparing the anodizable Al-Zn-Mn-Mg series cast-forged aluminum alloy of Example 7, the forming process includes low-pressure filling casting forming process, in-situ first-stage forging process, in-situ second-stage forging pre-deformation process, and aging process.

[0099] In the low-pressure filling casting process, the filling speed is 0.5 m / s, the filling time is 6 s, the casting pressure is 10 MPa, the holding time is 10 s, the mold temperature is 300℃, the alloy casting temperature is 700℃, and the cooling rate is 10℃ / s. In the in-situ primary forging process, the forging temperature is 540℃, the forging specific pressure is 50 MPa, the forging start time is 3 s, the holding time is 10 s, the cooling rate is 20℃ / s, and the deformation is 10%. In the in-situ secondary forging pre-deformation process, the forging temperature is 250℃, the forging specific pressure is 100 MPa, the holding time is 1 s, the cooling rate is 60℃ / s, and the deformation is 5%. In the aging treatment, the temperature is 100℃, and the time is 30 h.

[0100] When preparing the anodizable Al-Zn-Mn-Mg series cast-forged aluminum alloy of Example 8, the forming process includes low-pressure filling casting forming process, in-situ first-stage forging process, in-situ second-stage forging pre-deformation process, and aging process.

[0101] In the low-pressure filling casting process, the filling speed is 0.5 m / s, the filling time is 6 s, the casting pressure is 10 MPa, the holding time is 10 s, the mold temperature is 300℃, the alloy casting temperature is 700℃, and the cooling rate is 10℃ / s. In the in-situ primary forging process, the forging temperature is 570℃, the forging specific pressure is 50 MPa, the forging start time is 3 s, the holding time is 15 s, the cooling rate is 10℃ / s, and the deformation is 10%. In the in-situ secondary forging pre-deformation process, the forging temperature is 420℃, the forging specific pressure is 100 MPa, the holding time is 10 s, the cooling rate is 30℃ / s, and the deformation is 5%. In the aging treatment, the temperature is 110℃, and the time is 30 h.

[0102] When preparing the anodizable Al-Zn-Mn-Mg series cast-forged aluminum alloy of Example 9, the forming process includes low-pressure filled casting forming process, in-situ first-stage forging process, in-situ second-stage forging pre-deformation process, and solution treatment.

[0103] In the low-pressure filling casting process, the filling speed is 0.6 m / s, the filling time is 5 s, the casting pressure is 10 MPa, the holding time is 3 s, the mold temperature is 220℃, the alloy casting temperature is 710℃, and the temperature cooling rate is 20℃ / s. In the in-situ primary forging process, the forging temperature is 590℃, the forging specific pressure is 200 MPa, the forging start time is 2 s, the holding time is 6 s, the temperature cooling rate is 30℃ / s, and the deformation is 26%. In the in-situ secondary forging pre-deformation process, the forging temperature is 410℃, the forging specific pressure is 150 MPa, the holding time is 0 s, the temperature cooling rate is 20℃ / s, and the deformation is 6%. In the solution treatment, the temperature is 470℃ for 10 h, and in the aging treatment, the temperature is 90℃ for 30 h.

[0104] When preparing the anodizable Al-Zn-Mn-Mg series cast-forged aluminum alloy of Example 10, the forming process includes low-pressure filled casting forming process, in-situ first-stage forging process, in-situ second-stage forging pre-deformation process, and solution treatment.

[0105] In the low-pressure filling casting process, the filling speed is 0.6 m / s, the filling time is 5 s, the casting pressure is 10 MPa, the holding time is 3 s, the mold temperature is 220℃, the alloy casting temperature is 710℃, and the cooling rate is 20℃ / s. In the in-situ primary forging process, the forging temperature is 610℃, the forging specific pressure is 250 MPa, the forging start time is 2 s, the holding time is 10 s, the cooling rate is 20℃ / s, and the deformation is 35%. In the in-situ secondary forging pre-deformation process, the forging temperature is 410℃, the forging specific pressure is 100 MPa, the holding time is 0 s, the cooling rate is 20℃ / s, and the deformation is 10%. In the solution treatment, the temperature is 450℃ and the time is 20 h. In the aging treatment, the temperature is 100℃ and the time is 30 h.

[0106] In preparing the anodizable Al-Zn-Mn-Mg die-cast aluminum alloy of Example 11, the forming process includes die-casting the alloy liquid at a temperature of 640ºC, wherein the die-casting speed of the die-casting machine is 2.1 m / s and the temperature cooling rate is 70 K / s.

[0107] When preparing the anodizable Al-Zn-Mn-Mg die-cast aluminum alloy of Example Twelve, the forming process includes die-casting the alloy liquid at a temperature of 670ºC, wherein the die-casting speed of the die-casting machine is 2m / s and the temperature cooling rate is 90K / s.

[0108] When preparing the anodizable Al-Zn-Mn-Mg vacuum die-cast aluminum alloy of Example Thirteen, the forming process includes vacuum die-casting the alloy liquid at a temperature of 680ºC, with a vacuum degree of 30mbar, an injection speed of 3m / s, a casting pressure of 115MPa, and a temperature cooling rate of 200K / s.

[0109] When preparing the anodizable Al-Zn-Mn-Mg vacuum die-cast aluminum alloy of Example Fourteen, the forming process includes vacuum die-casting the alloy liquid at a temperature of 640ºC, a vacuum degree of 60mbar, an injection speed of 5m / s, a casting pressure of 100MPa, and a temperature cooling rate of 140K / s.

[0110] Table 2 Performance test results of aluminum alloys in Examples 1 to 14 Referring to Table 2, the anodizable Al-Zn-Mn-Mg die-cast aluminum alloys of Examples 1 to 14 exhibit excellent tensile strength, yield strength, and elongation. Specifically, the anodizable Al-Zn-Mn-Mg cast-forged aluminum alloys of Examples 1 to 10 have a tensile strength of not less than 360 MPa, a yield strength of not less than 240 MPa, and an elongation of not less than 12%; the anodizable Al-Zn-Mn-Mg die-cast aluminum alloys of Examples 11 and 12 have a tensile strength of not less than 310 MPa, a yield strength of not less than 170 MPa, and an elongation of not less than 13%; and the anodizable Al-Zn-Mn-Mg vacuum die-cast aluminum alloys of Examples 13 and 14 have a tensile strength of not less than 320 MPa, a yield strength of not less than 180 MPa, and an elongation of not less than 14%. This indicates that the anodizable Al-Zn-Mn-Mg aluminum alloys of the present invention possess superior comprehensive performance.

[0111] When an anodized film of 200 mm is formed on the surface of the anodizable Al-Zn-Mn-Mg die-cast aluminum alloys of Examples 1 to 14, the anodized film has better transparency, gloss and color uniformity, so that the anodizable Al-Zn-Mn-Mg die-cast aluminum alloys of Examples 1 to 10 can present a better appearance.

[0112] In summary, the anodizable Al-Zn-Mn-Mg series cast-forged aluminum alloys of the present invention have a tensile strength of not less than 360 MPa, a yield strength of not less than 240 MPa, and an elongation of not less than 12%; the anodizable Al-Zn-Mn-Mg series die-cast aluminum alloys of the present invention have a tensile strength of not less than 310 MPa, a yield strength of not less than 170 MPa, and an elongation of not less than 13%; the anodizable Al-Zn-Mn-Mg series vacuum die-cast aluminum alloys of the present invention have a tensile strength of not less than 320 MPa, a yield strength of not less than 180 MPa, and an elongation of not less than 14%. Furthermore, the various anodizable Al-Zn-Mn-Mg series high-strength aluminum alloys of the present invention also possess excellent anodizing performance.

[0113] The above are merely preferred embodiments of the present invention and do not limit the scope of the patent. Any equivalent structural transformations made using the content of the present invention under the inventive concept of the present invention, or direct / indirect applications in other related technical fields, are included within the scope of patent protection of the present invention.

Claims

1. An anodizable Al-Zn-Mn-Mg die-cast aluminum alloy, containing Al, characterized in that, The anodizable Al-Zn-Mn-Mg die-cast aluminum alloy further contains 2-4.5% Zn, 0.01-0.8% Si, 0.001-0.5% Fe, 0.001-0.3% Cu, 1-3% Mn, 0.8-4% Mg, 0.001-0.05% B, and [other components not specified in the original text]. The anodizable Al-Zn-Mn-Mg die-cast aluminum alloy comprises 0.001-0.05% Sn, 0.001-0.2% Sb, 0.001-0.1% In, and 0.001-0.5% Bi. The alloy undergoes a forming process, which includes the following steps: the forming process is a die-casting process, the die-casting temperature is 640-720ºC, and the die-casting speed is 0.23-2.5 m / s.

2. The anodizable Al-Zn-Mn-Mg die-cast aluminum alloy according to claim 1, characterized in that, The anodizable Al-Zn-Mn-Mg die-cast aluminum alloy contains 2-4% Zn, 0.1-0.8% Si, 0.01-0.5% Fe, 0.01-0.3% Cu, 1-2.5% Mn, 1-4% Mg, 0.001-0.05% B, 0.001-0.05% Sn, 0.001-0.2% Sb, 0.001-0.1% In, and 0.001-0.5% Bi.

3. The anodizable Al-Zn-Mn-Mg die-cast aluminum alloy according to claim 1, characterized in that, The anodizable Al-Zn-Mn-Mg die-cast aluminum alloy further contains at least one of Ag, Zr, Mo, C, V, Li, Nb, Co, Ca, Sr, Ge, Cr, Ni, Ti, RE, AlTiC, AlTiB, BN, and SiC, wherein the mass percentage content of Ag is 0.01-0.1%; the mass percentage content of Zr is 0.01-0.3%; the mass percentage content of Mo is 0.001-0.2%; the mass percentage content of C is 0.0001-0.0002%; the mass percentage content of V is 0.001-0.3%; the mass percentage content of Li is 0-0.05%; and the mass percentage content of Nb is 0.01-0.05%. The mass percentage content is 0-0.3%; the mass percentage content of Co is 0-0.5%; the mass percentage content of Ca is 0.0001-0.2%; the mass percentage content of Sr is 0-0.05%; the mass percentage content of Ge is 0-0.1%; the mass percentage content of Cr is 0-0.3%; the mass percentage content of Ni is 0-0.2%; the mass percentage content of Ti is 0-0.2%; the mass percentage content of RE is 0-0.3%; the mass percentage content of AlTiC is 0-5%; the mass percentage content of AlTiB is 0-5%; the mass percentage content of BN is 0-5%; and the mass percentage content of SiC is 0-15%.

4. The anodizable Al-Zn-Mn-Mg die-cast aluminum alloy according to claim 3, characterized in that, The anodizable Al-Zn-Mn-Mg die-cast aluminum alloy contains Ag, Zr and RE, with Ag accounting for 0.01-0.1% by mass, Zr accounting for 0.01-0.3% by mass, and RE accounting for 0.01-0.3% by mass.

5. The anodizable Al-Zn-Mn-Mg die-cast aluminum alloy according to claim 3, characterized in that, The anodizable Al-Zn-Mn-Mg die-cast aluminum alloy contains Mo, Zr and C, with Mo accounting for 0.001-0.2% by mass, Zr accounting for 0.01-0.3% by mass, and C accounting for 0.001-0.002% by mass.

6. The anodizable Al-Zn-Mn-Mg die-cast aluminum alloy according to claim 3, characterized in that, The anodizable Al-Zn-Mn-Mg die-cast aluminum alloy contains Mo, Zr and V, with Mo accounting for 0.001-0.2% by mass, Zr accounting for 0.01-0.3% by mass, and V accounting for 0.001-0.3% by mass.

7. The anodizable Al-Zn-Mn-Mg die-cast aluminum alloy according to claim 3, characterized in that, The anodizable Al-Zn-Mn-Mg die-cast aluminum alloy contains AlTiC, AlTiB, SiC and BN, with AlTiC having a mass percentage content of 0.1-1%, AlTiB having a mass percentage content of 0.1-1%, SiC having a mass percentage content of 0.1-6%, and BN having a mass percentage content of 0.1-1%.

8. A method for preparing anodizable Al-Zn-Mn-Mg die-cast aluminum alloy, comprising the following steps: It provides Zn source, Si source, Fe source, Cu source, Mn source, Mg source, B source, Sn source, Sb source, In source, Bi source, and Al source; The Al source is heated to obtain Al liquid; Add Zn source, Si source, Fe source, Cu source, Mn source, Mg source, B source, Sn source, Sb source, In source and Bi source to the Al liquid to obtain an alloy liquid; and The alloy liquid is subjected to a forming process to obtain an anodizable Al-Zn-Mn-Mg die-cast aluminum alloy. The forming process includes the following steps: the forming process is a die-casting process, the die-casting temperature is 640-720ºC, and the die-casting speed is 0.23-2.5m / s. The anodizable Al-Zn-Mn-Mg die-cast aluminum alloy contains 2-4.5% Zn and 0.01-0.8% Si by mass. The content of Fe is 0.001-0.5% by mass, Cu is 0.001-0.3% by mass, Mn is 1-3% by mass, Mg is 0.8-4% by mass, B is 0-0.05% by mass, Sn is 0-0.05% by mass, Sb is 0-0.2% by mass, In is 0-0.1% by mass, and Bi is 0-0.5% by mass.

9. The method for preparing anodizable Al-Zn-Mn-Mg die-cast aluminum alloy according to claim 8, characterized in that, The method for preparing the anodizable Al-Zn-Mn-Mg die-cast aluminum alloy further includes the step of adding at least one of the following sources to the Al liquid: Ag source, Zr source, Mo source, C source, V source, Li source, Nb source, Co source, Ca source, Sr source, Ge source, Cr source, Ni source, Ti source, RE source, AlTiC source, AlTiB source, BN source, and SiC source. In the anodizable Al-Zn-Mn-Mg die-cast aluminum alloy, the mass percentage content of Ag is 0.01-0.1%; the mass percentage content of Zr is 0.01-0.3%; the mass percentage content of Mo is 0.001-0.2%; the mass percentage content of C is 0.0001-0.0002%; and the mass percentage content of V is 0.001%. -0.3%; Li mass percentage content is 0-0.05%; Nb mass percentage content is 0-0.3%; Co mass percentage content is 0-0.5%; Ca mass percentage content is 0.0001-0.2%; Sr mass percentage content is 0-0.05%; Ge mass percentage content is 0-0.1%; Cr mass percentage content is 0-0.3%; Ni mass percentage content is 0-0.2%; Ti mass percentage content is 0-0.2%; RE mass percentage content is 0-0.3%; AlTiC mass percentage content is 0-5%; AlTiB mass percentage content is 0-5%; BN mass percentage content is 0-5%; SiC mass percentage content is 0-15%.

10. An aluminum alloy structural component, characterized in that, The material of the aluminum alloy structural component is an anodizable Al-Zn-Mn-Mg die-cast aluminum alloy as described in any one of claims 1-7 or an Al-Zn-Mn-Mg aluminum alloy prepared by the preparation method of anodizable Al-Mn-Mg aluminum alloy as described in any one of claims 8-9.